130k views
3 votes
Match each equation with the slope (m) and y-intercept (b) m:-6, b:(0,5) m:-5/6, b:(0,1)m:5/6, b:(0,1)m:5/6, b:(0,-1)y=5-6xy=(5/6)x +15x-6y=65x+6y=6

1 Answer

6 votes

Ok, so

First of all, remember that a line can be described by two forms:

1. y = mx+b, where m is the slope and b is the y - intercept-

2. We would have the general equation for a line, which is:

Ax + By + C = 0

Where m(slope) is -A/B and the intercept (b) is -C/B.

Now, let's find the slope and y - intercept for each line here below.

a. y = 5 - 6x

Here we have a line which has the first form (1). So, if we rewrite:

y = - 6x + 5.

So, If we compare with the first equation, we notice that m = -6 and b = 5

or, m = -6 and b = (0,5)

b. y = (5/6)x + 1

Here we have a line which has the first form (1).

So, if we compare, we notice that m = 5/6 and b = 1, or, m = 5/6 and b = (0,1)

c. 5x - 6y = 6

If we rewrite the equation:

5x - 6y - 6 = 0

Here we have a line which has the second form (2).

We know that

A = 5

B = -6

C = -6

If we replace, m = -A/B, which is -(5) / (-6) , and this is 5/6.

And, y intercept will occurs at y = -C/B, which is -(-6) / -6, which is 6/-6, or -1.

So, the slope will be 5/6 and y-intercept (0,-1).

m = 5/6 and b = (0,-1)

d. 5x + 6y = 6

If we rewrite the equation:

5x + 6y - 6 = 0

Here we have a line which has the second form (2).

We know that:

A = 5

B = 6

C = -6

If we replace, m = -A/B, which is -(5) / 6, so, m = -5/6

And, y intercept will occurs at y = -C/B, which is -(-6) / 6, so, b = 1

Finally, m = -5/6, and b = (0,1)